2006
DOI: 10.1080/00222930500219258
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of long-term occupational performance outcomes for adults after moderate to severe traumatic brain injury

Abstract: The study supports the use of a comprehensive model for long-term outcomes after TBI where pre-injury characteristics and post-injury cognitive and physical characteristics account for the greatest proportion of explained variance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 53 publications
4
28
0
1
Order By: Relevance
“…Previous studies on the long-term effects of TBI have focused on a broad range of outcomes such as chronic health conditions, quality of life and use of health services [5][6][7][8][9]. Research has shown that persons with TBI have higher than normal prevalence of long-term adverse outcomes including various chronic health conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the long-term effects of TBI have focused on a broad range of outcomes such as chronic health conditions, quality of life and use of health services [5][6][7][8][9]. Research has shown that persons with TBI have higher than normal prevalence of long-term adverse outcomes including various chronic health conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Research studies have shown that PTSD and TBI can negatively affect functional performance and quality of life (Carlson et al, 2011;Devitt et al, 2006;Lopez, 2011;Phipps & Richardson, 2007;Plach & Sells, 2013). Additionally, several studies have found that both actual participation and self-perceived satisfaction with participation in meaningful occupations are associated with increased psychological health and subjective well-being (Bejerholm & Eklund, 2007;Christiansen, Backman, Little, & Nguyen, 1999;Eklund & Leufstadius, 2007;Iannelli & Wildin, 2007).…”
mentioning
confidence: 99%
“…These measures have been useful in measuring occupational performance outcomes (Devitt et al, 2006). According to a nationwide telephone survey, occupational therapy staff were also involved in 69% of all home-based CI programs (Glenn, Rotman, Goldstein, & Selleck, 2005).…”
mentioning
confidence: 99%
“…The participation concept is the third domain of the ICF and has been studied extensively in rehabilitation research. During the past decade, studies focusing on CI and TBI have increased, and outcome studies on TBI, specifically on CI, have provided insight into potential predictors of successful CI (Devitt et al, 2006;O'Connor, 2002). However, no systematic reviews exist of intervention programs that enhance CI for the TBI population.…”
mentioning
confidence: 99%